Determinant factors of brand loyalty in Malaysian automotive industry / Khaled Alqasa, Tuck Sum Ho and Filzah Md Isa - Alqasa, Khaled; Tuck, Sum Ho; Md Isa, Filzah (UiTM Press, 2017)
With the rapid growth in the Malaysian automotive industry, brand loyalty has become a major issue for a majority of the automobile brands. Market shares for national brand automobiles had been on the declining stage since 2011, from 56.4 per cent to 46.8 per cent in 2014. The objectives of this study are to verify the factors that affect consumers' perception towards brand loyalty by studying the relationships between three important factors: which are service quality, marketing-mix strategy, and country-of-origin, on brand loyalty. A postal mail survey using judgmental, cluster and simple random sampling of Malaysian consumers in the Klang Valley yielded 413 respondents of which 381 samples are usable. Regression was used to analyse the relationships between the variables. Results showed that marketing-mix strategy and country-of-origin have significant relationships with brand loyalty. However, service quality does not have any significant relationship with brand loyalty. The findings of this study, while contributing to the body of knowledge may also assist policy makers and marketers in their sustainability efforts.